Analysis of Coffee Business Development Strategy in the Sumber Kembang Farmer Group Using the SWOT Method to Achieve Global Competitiveness - Ardhiarisca, Oryza; Faizin, Nur; Putra, Rediyanto; Yuana, Dia Bitari Mei; Lestari, Datik (P3M Politeknik Negeri Jember, 2024)
Coffee cultivation plays a pivotal role in global agricultural trade, offering cultural, economic, and social value that transcends borders. In Indonesia, particularly in Jember Regency, coffee stands out as a leading agricultural product, supporting local economies and contributing significantly to global coffee exports. Within this context, the Sumber Kembang Farmer Group cultivates and processes coffee, offering a diverse range of products, including coffee logs and ground coffee, derived from both Robusta and Arabica varieties and processed through various methods. This research aims to identify optimal strategies for developing the group's coffee business. A case study approach was employed, with data collected through interviews, observations, and a literature review. The analysis used several strategic tools, including the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, Internal-External (IE) Matrix, SWOT (Strengths, Weaknesses, Opportunities, Threats) Matrix, and Quantitative Strategic Planning Matrix (QSPM). The findings reveal that the coffee enterprise of the Sumber Kembang Farmer Group is positioned in quadrant IV of the IE matrix, indicating a Growth and Build strategy. This positioning underscores the need for an extensive and integrative approach encompassing six strategic components. Prioritizing the improvement of product marketing quality is identified as a critical step toward achieving business development goals.